Eating behaviour in Swiss preschool children-Validation of a German and a French version of the Children's Eating Behaviour Questionnaire (CEBQ). - Anaëlle L Leuba; Andrea H Meyer; Tanja H Kakebeeke; Kerstin Stülb; Amar Arhab; Annina E Zysset; Claudia S Leeger-Aschmann; Einat A Schmutz; Susi Kriemler; Oskar G Jenni; Jardena J Puder; Simone Munsch; et al. (PLoS ONE, 2023)
Young children's eating behavior is crucial for any further development of healthy eating. Early eating behavior are often assessed through parental report. The Children's Eating Behaviour Questionnaire (CEBQ) is a widely used parental questionnaire that has been validated in families of different gender, age and cultural background. Research has shown that the 8-factor structure has some inconsistencies and sample characteristics such as age, gender, and culture can influence the results. To which extent such sample characteristics might influence results within a multi-lingual culture has not been investigated so far. Therefore, the aim of the study was to evaluate the factor structure of the CEBQ among 511 preschool children of the French and German parts of Switzerland, aged 2 to 6 years (Mean 3.85 years; SD 0.69). Confirmatory Factor Analysis showed a modified structure of the original questionnaire, with a 7-factor structure providing a reasonable fit to the data (TLI = 0.954, CFI = 0.952, RMSEA = 0.063 and SRMR = 0.067). The subscale 'Desire to drink' was removed, and a few items moved to other subscales as they loaded higher on a different subscale compared to the original model. Reliabilities based on the coefficient omega were acceptable to satisfying across the seven factors, ranging from 0.66 to 0.90. There were no significant gender or age differences, but French speaking children showed higher levels of 'Satiety responsiveness' and lower 'Enjoyment of food' than German speaking children. Yet, these effects were small. The German and French CEBQ are valid and reliable versions of the original CEBQ and can be used in a multicultural context.